Cultural chanracteristics of the h'mong ethnic people northwestern area of vietnam - Nguyễn Thị Loan Anh (2021)
Within the scope of this paper, then author presents two main points. The fierst point is the identity of the H'mong ethnic groupn in the North West , The second point ic the cultural characteristics of H'mong people . finally. the author mentions the conclusion and bibliography